(untitled) (Journal of Medicine, 2016)
Hypertension is a major public health problemglobally in both the developed and developing countries. Hypertension leads to cardiovascular diseases, stroke, kidney failure and is the leading cause of mortality and morbidity globally. The risk factors for hypertension, which can mostly be prevented through simple health promotion and preventive measures are mostly known. However, papers documenting the strategies for prevention of hypertension in Bangladesh is not available. The aim of this review study was to identify and discuss different approaches to prevent hypertension in Bangladesh. We performed a systematic search using electronic as well as manual method for published and unpublished reports of prevention of hypertension. We then identified and discussed prevention strategies for hypertension suitable for Bangladesh context. Although several methods have shown to prevent hypertension, the challenge remains in implementing these methods in resource poor settings. Integrated action based on comprehensive policy and stepwise implementation should be adopted taking into consideration of local needs. Hypertension prevention should focus on awareness generation, health promotion and reduction of common risk factors using a combination of population based approach and targeted individual interventions. Consorted actions should be taken as a priority to prevent hypertension through intersectoral, multidisciplinary and multilevel approach by the Government, Non-Government Organizations (NGOs), civil societies and create greater awareness among the population for a healthy life-style. J MEDICINE January 2016; 17 (1) : 30-35